The role of social media in glorifying criminal activities among Nigerian youth in the Marlian Empire - Ayobolu, Yetunde Oluwayemisi (International Journal of Communication and Society, 2024)
Social media platforms have become powerful tools for information dissemination and personal branding that mold shape and influence the public. Influencers and public figures leverage these networks to showcase their lifestyles and connect with audiences, particularly young people who often aspire to emulate their favorite personalities. The glorification of criminal activity on social media can inspire others to engage in similar behaviors, as in the case of the Marlian Empire in Nigeria. This study examined the complexities of the Marlian Empire’s cultural influence on the youth, by investigating how it shapes their perceptions, influences behaviors, and whether it poses a challenge to established norms of the society. The study is quantitative, adopting the descriptive survey method with questionnaires utilised as data gathering instrument from 150 undergraduates selected through simple random sampling method from Koladaisi University, Ibadan. Results from the data were analysed using the SPSS, and were presented in figures and illustrations. Findings indicate that social media played a significant role in the influence that the Marlian Empire presently has with majority of their followers emulating their lifestyle and attitude as portrayed online. The study concludes that portrayal of the celebrity culture mostly has negative impacts on the lives of youths in Nigeria and some of these unpleasant activities have been normalised. The study recommends that influential figures be encouraged to use their platforms to promote positive messages that positively influence youth behavior for proper development and growth.